Acellular Dermal Matrices: Applications in Plastic Surgery - Tork, Shahryar; Jefferson, Ryan C.; Janis, Jeffrey E. (Seminars in Plastic Surgery, 2019)
Modern advances in tissue engineering have transformed the plastic surgeon's management strategies across a wide variety of applications. Comprehension of the fundamentals of biologic constructs is critical to navigating the available armamentarium. It is essential that plastic surgeons become familiar with some of the existing methods for utilizing biologics as well as the advantages and limitations to their use. In this article, the authors describe the basic science of biologics with a focus on acellular dermal matrices (ADMs), and review the recent evidence behind their use for a variety of reconstructive and aesthetic purposes. The review is organized by system and examines the common indications, techniques, and outcomes pertaining to the application of ADMs in select anatomic areas. The final section briefly considers possible future directions for using biologics in plastic and reconstructive surgery.
Keywords: Biologics; acellular dermal matrix; plastic surgery; reconstructive surgery